Prevalence of Cholesteatoma and its Complications in Patients of Chronic Suppurative Otitis Media - Muhammad Musharaf Baig , Muhammad Ajmal ,Ifra Saeed , Syeda Fatima (Journal of Rawalpindi Medical College, 2011)
Background: To determine the prevalence of cholesteatoma and its complications in patients suffering from chronic suppurative otitis media(CSOM). Methods: In this prospective observational study 160 patients of CSOM were selected randomly. They were put on conservative treatment. Forty patients did not respond to the regimen and they had to undergo mastoid exploration. The latter were observed for cholesteatoma, granulation tissue, aural polyps and other complications. Results: Majority (69%) of the patients belonged to lower socioeconomic status. Mean age of the patients was 29+14.26 years, ranging from 1-80 years. Cholesteatoma was diagnosed in 10.63%. An unusual finding was observed in one patient who had marginal perforation, but per operatively showed no cholesteatoma. The most common complication was ossicular damage (13.5%). Intracranial complications were seen in 4 cases. Conclusion:Cholesteatoma was found to be associated with most of the complications in CSOM